(untitled) (Alternautas, 2016)
Since the 1990s, foreign investment has been presented as a strong means for development. Foreign investment serves to climb the value ladder, bridge the investment gap, and maintain a ‘maxim effective utilization of economic resources.’ Yet, attracting and enabling foreign investment is not an easy task for governments. In a context of fierce competition for capital, this requires an active state promoting policies that match the needs of foreign investors. As a result, the control and steering of foreign investment of the 1960s and 1970s was quickly replaced with a model in which governments must facilitate foreign investor initiatives and reap the benefits of multinational corporate activity. This short essay aims to illustrate this more general debate by looking at the awards in the case Occidental Petroleum (Oxy) II v Ecuador, where the tribunal imposed one of the highest awards against a host state.